Genotoxic Profile and Morphological Variation of the Amanita rubescens Complex: Traditional Knowledge for Safe Consumption in Mexico - Griselda Nallely Hernández-Rico; Pablo Octavio-Aguilar; Roberto Orijel-Garibay; Leticia Romero-Bautista (Ethnobiology Letters, 2019)
Wild mushrooms are important to the nutritional health and economic subsistence of rural populations in Mexico, but inaccurate identification of mushrooms has led to reported cases of poisoning. The aim of this study is to establish genotoxic profiles of mushrooms of the putative Amanita rubescens complex and to link those profiles with morphological attributes that suggest a correct identification of mushrooms, in order to prevent poisoning. Several combinations of amplification products (AMA, PHA, POP1, and POP2 genes) were identified in A. rubescens fungi sold in traditional markets; these genes are related to the presence of toxic polypeptides and its enzymatic regulators. The sequences correspond to a previously reported toxic gene family (MSDIM). All samples with the complete toxic gene profile presented reddish to dark-brown sporomes; this is the only attribute that visually distinguishes samples with toxic potential. Our results suggest that the mushrooms sold in traditional Mexican markets do not correspond to the A. rubescens complex. We conclude that morphological variability allows for identification of edible and inedible mushrooms.